DPT vaccine evolution: Formulation differences, standardisation issues, and development prospects - E. I. Komarovskaya; O. V. Proskurina; A. A. Soldatov (Биопрепараты: Профилактика, диагностика, лечение, 2025)
INTRODUCTION. Currently, diphtheria, pertussis, and tetanus (DTP) vaccines are available in tetra-, penta-, and hexavalent combinations with inactivated poliomyelitis, Haemophilus influenzae, and hepatitis B components. Despite the widespread introduction of DTP vaccines in national vaccination programmes, concerns remain about the immunogenicity and safety of the pertussis component, the standardisation of vaccine production and quality control methods, and the inclusion of DTP vaccines in national routine vaccination schedules.AIM. This study aimed to provide an updated overview of DTP-based combined vaccines and analyse the current challenges associated with their use and quality improvement.DISCUSSION. DTP vaccines hold a  central  place  in  national  routine  vaccination  schedules. The development of numerous safe and effective DTP vaccines has contributed to the formulation of DTP-based combined vaccines that include additional components and are suitable for infants. The addition of inactivated components against poliomyelitis, H. influenzae, and hepatitis B has facilitated the introduction of DTP-based combined vaccines into the recommended vaccination programmes and has reduced the number of injections received by a child. However, DTP-based combined vaccines from different manufacturers differ in the composition and  quantity  of  antigens  and  in  quality  control  methods.  The  key  differences in the composition of these vaccines are due to the inclusion of either whole-cell or acellular pertussis. The current global rise in the incidence of pertussis is associated with the widespread use of acellular vaccines, which do not induce long-term immunity. This review considers the mutual influence of antigens in relation to vaccine efficacy and safety and addresses the standardisation issues associated with antigen production and quality control. The article analyses data on various DTP-based combined vaccines and the quantity of antigens in them. The review discusses promising areas for further improvement of the quality and effectiveness of DTP-based combined vaccines.CONCLUSIONS. Addressing unresolved standardisation issues in the production and quality control of DTP-based combined vaccines, which (along with country-specific licensing requirements) limit the international exchange of vaccines, can facilitate international recognition and ensure a high level of potency and safety of DTP-based combined vaccines.